Post-correlation on-lamella cryo-CLEM reveals the membrane architecture of lamellar bodies - Klein, Steffen; Wimmer, Benedikt; Winter, Sophie L.; Kolovou, Androniki; Laketa, Vibor; Chlanda, Petr (Communications biology, 2021)
Lamellar bodies (LBs) are surfactant-rich organelles in alveolar cells. LBs disassemble into a lipid-protein network that reduces surface tension and facilitates gas exchange in the alveolar cavity. Current knowledge of LB architecture is predominantly based on electron microscopy studies using disruptive sample preparation methods. We established and validated a post-correlation on-lamella cryo-correlative light and electron microscopy approach for cryo-FIB milled cells to structurally characterize and validate the identity of LBs in their unperturbed state. Using deconvolution and 3D image registration, we were able to identify fluorescently labeled membrane structures analyzed by cryo-electron tomography. In situ cryo-electron tomography of A549 cells as well as primary Human Small Airway Epithelial Cells revealed that LBs are composed of membrane sheets frequently attached to the limiting membrane through “T”-junctions. We report a so far undescribed outer membrane dome protein complex (OMDP) on the limiting membrane of LBs. Our data suggest that LB biogenesis is driven by parallel membrane sheet import and by the curvature of the limiting membrane to maximize lipid storage capacity.